The manometric profile of the gastroesophageal area.: Value of same in respiratory pathology by reflux. - Balboa, Oscar; Santurtún, Paz (Cirugía del Uruguay, 1985)
Presenling an interpretalion of the esophagogaslric manometric pattern by means of a manometric profile. Analysis of a group of 114 patients with respiratory pathology and suspected of being affected by gastroesophageal reflux and also studied with radiology, endoscopy and scintillography. The study ol !he mano• metric profile has a 83% sensibility and is quite specific.